Properties study of fish collagen and gelatin blend for high-temperature food applications - Chay, Jie Cheng (Nanyang Technological University, 2022)
Sustainable food production is becoming a necessity due to the overwhelming demand for global resources. In meeting these demands, an equivalent amount of waste is being generated at the same time. In aquaculture, for instance, staggering amounts of fisheries wastes – primarily skins, were left accumulated in the processing industries. These wastes contain valuable bioresources that can be contributed back to the supply chain for functional food developments. This study adopts the concept of waste valorization to recover collagen-I from Barramundi fish skins. A remarkable collagen yield of 74.57 % was obtained by acetic acid solubilization, with a modest pretreatment concentration responsible for the increased yield. FTIR analysis reveals its intact triple-helical structure, against gelatin from subsequent extraction. At present, sustainable utilization of fish collagen has been limited by its ease of denaturation. Especially in the field of food applications, where extreme heating conditions are often involved. This study may be the first to formulate an edible collagen-based gel, that is stable for boiling at 100 ˚C. MTGase was involved to crosslink collagen with gelatin enzymatically, for increased crosslinking density. Synergistically, the collagen reinforces gelatin gels with excellent chewiness from 5.85 to 36.51 kPa, which is an important texture indicator for meat and fish products. The findings elucidated that textural properties are closely dependent on the collagen helices, rather than the crosslinking density that contributed to enhanced thermal stability. Overall, the blended gel demonstrates improved viability for high-temperature food applications, along with textures useful for functional food developments.